Analisis Tentang Tindakan Penagihan Yang Melawan Hukum Terkait Pinjaman Online dari Fintech Ilegal (Studi Kasus Atas Putusan Nomor 438/Pid.Sus/2020/PN.Jkt.Utr) - Alfin Rafael; Sugandi Ishak (Fakultas Hukum Universitas Tarumanagara, 2021)
In Indonesia, there are 3,107 illegal fintech companies. The author focuses on illegal collection actions related to online loans from illegal fintech as stated in Decision Number 438/Pid.Sus/2020/PN.Jkt.Utara. When collecting an online loan from the victim, the defendant used harsh words towards the victim by sending a voice note via Whatsapp with words such as